Both Biosynthesis and Transport Are Involved in Glucosinolate Accumulation During Root-Herbivory in Brassica rapa - Touw, Axel J.; Verdecia Mogena, Arletys; Maedicke, Anne; Sontowski, Rebekka; van Dam, Nicole M.; Tsunoda, Tomonori (Frontiers in Plant Science, 2020)
The optimal defense theory predicts that plants invest most energy in those tissues that have the highest value, but are most vulnerable to attacks. In Brassica species, root-herbivory leads to the accumulation of glucosinolates (GSLs) in the taproot, the most valuable belowground plant organ. Accumulation of GSLs can result from local biosynthesis in response of herbivory. In addition, transport from systemic tissues by specialized GSL transporter proteins can play a role as well. GSL biosynthesis and transport are both inducible, but the role these processes play in GSL accumulation during root-herbivory is not yet clear. To address this issue, we performed two time-series experiments to study the dynamics of transport and biosynthesis in local and systemic tissues of brassicaceous plants. We exposed roots of Brassica rapa to herbivory by the specialist root herbivore Delia radicum for 7 days. During this period, we sampled above- and belowground plant organs 12 hours, 24 hours, 3 days and 7 days after the start of herbivory. Next, we measured the quantity and composition of GSLs together with the expression of genes involved in GSL biosynthesis and transport. We found that both benzyl and indole GSLs accumulate in the taproot during root-herbivory, whereas we did not observe any changes in aliphatic GSL levels. The rise in indole GSL levels coincided with increased local expression of biosynthesis and transporter genes, which suggest that both biosynthesis and GSL transport play a role in the accumulation of GSLs during root herbivory. However, we did not observe a decrease in GSL levels in systemic tissues. We therefore hypothesize that glucosinolate transporters help to retain GSLs in the taproot during root-herbivory.